Interference effects in nonplanar wires with a two-dimensional electron gas - Basmaji, P.; Gusev, G. M.; La Scala, N. [UNESP]; Gonzalez-Borrero, P. P.; Lubyshev, D. I.; Da Silva, M. P.A.; Maude, D. K.; Portal, J. C.; Pusep, Yu A.; Rossi, J. C. (My University, 1998)
We have studied the universal conductance fluctuations (UCF) due to quantum interface in a two-dimensional electron gas (2DEG) grown on the substrates with pre-patterned, sub-micron wires. The dependence of UCF on the angle between the direction of the magnetic field and the substrate has been investigated. We found, that magnetoresistance traces for different angles are completely uncorrelated. A non-planar character of electron motion is responsible for these angular conductance fluctuations. We compared the experimental results with a simple geometrical model.